2007
DOI: 10.1186/bcr1747
|View full text |Cite
|
Sign up to set email alerts
|

Application of the multicellular tumour spheroid model to screen PET tracers for analysis of early response of chemotherapy in breast cancer

Abstract: Introduction Positron emission tomography (PET) is suggested for early monitoring of treatment response, assuming that effective anticancer treatment induces metabolic changes that precede morphology alterations and changes in growth. The aim of this study was to introduce multicellular tumour spheroids (MTS) to study the effect of anticancer drugs and suggest an appropriate PET tracer for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Therefore, FLT uptake predominately reflects the fraction of proliferating cells. As has been reported frequently, docetaxel alone induced significant inhibition of [ 18 F]FLT uptake in tumor cells (41,42). Our study results (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, FLT uptake predominately reflects the fraction of proliferating cells. As has been reported frequently, docetaxel alone induced significant inhibition of [ 18 F]FLT uptake in tumor cells (41,42). Our study results (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Tam has been shown to decrease glycolysis [19,24,25] and inhibit GLUT 1 in vitro in tam-sensitive cells [19]. Previous studies have also shown a decrease in glycolysis after tam treatment by imaging FDG uptake [26,27]. Uptake of 2-NBDG significantly decreased after treatment in MCF7 cells, but did not change in the MDA-MB-435 cell line.…”
Section: Discussionmentioning
confidence: 96%
“…We have therefore previously advocated an empiric approach, in which the appropriate PET tracer is selected on the basis of cellular uptake studies performed in a spheroid cell culture model (8,9). The model presented here is optimized for this type of in vitro work.…”
Section: Discussionmentioning
confidence: 99%
“…The first part of this concept is illustrated by studies performed in multicellular cell aggregates (i.e., spheroids) (5)(6)(7)(8)(9). This cell culture mode was selected because it mimics better the cellular physiology of in vivo tumors than do monolayer cells, allows an easy application of pulse treatment or drug exposure mimicking the in vivo exposure, allows follow-up of drug effects during a longer time span than do monolayer cells (typically days to weeks), is practical for evaluation of effects on growth, is practical for application of PET tracers, and allows an assessment of PET tracer uptake and an evaluation of secreted or tissue biomarkers in the same sample.…”
mentioning
confidence: 99%